Modulation of Fronto-Striatal Functional Connectivity Using Transcranial Magnetic Stimulation - Alkhasli, Isabel; Sakreida, Katrin; Mottaghy, Felix M.; Binkofski, Ferdinand (Frontiers in Human Neuroscience, 2019)
Background: The fronto-striatal network is involved in various motor, cognitive, and emotional processes, such as spatial attention, working memory, decision-making, and emotion regulation. Intermittent theta burst transcranial magnetic stimulation (iTBS) has been shown to modulate functional connectivity of brain networks. Long stimulation intervals, as well as high stimulation intensities are typically applied in transcranial magnetic stimulation (TMS) therapy for mood disorders. The role of stimulation intensity on network function and homeostasis has not been explored systematically yet. Objective: In this pilot study, we aimed to modulate fronto-striatal connectivity by applying iTBS at different intensities to the left dorso-lateral prefrontal cortex (DLPFC). We measured individual and group changes by comparing resting state functional magnetic resonance imaging (rsfMRI) both pre-iTBS and post-iTBS. Differential effects of individual sub- vs. supra-resting motor-threshold stimulation intensities were assessed. Methods: Sixteen healthy subjects underwent excitatory iTBS at two intensities [90% and 120% of individual resting motor threshold (rMT)] on separate days. Six-hundred pulses (2 s trains, 8 s pauses, duration of 3 min, 20 s) were applied over the left DLPFC. Directly before and 7 min after stimulation, task-free rsfMRI sessions, lasting 10 min each, were conducted. Individual seed-to-seed functional connectivity changes were calculated for 10 fronto-striatal and amygdala regions of interest with the SPM toolbox DPABI. Results: Sub-threshold-iTBS increased functional connectivity directly between the left DLPFC and the left and right caudate, respectively. Supra-threshold stimulation did not change fronto-striatal functional connectivity but increased functional connectivity between the right amygdala and the right caudate. Conclusion: A short iTBS protocol applied at sub-threshold intensities was not only sufficient, but favorable, in order to increase bilateral fronto-striatal functional connectivity, while minimizing side effects. The absence of an increase in functional connectivity after supra-threshold stimulation was possibly caused by network homeostatic effects.